Learning styles and academic performance in the operational research subject of students of the IV cycle of the Faculty of Administrative Sciences of the National - Gonzales Agama, Nelly Aurelia (2020)
The objective of the research has been to determine the relationship that exists between learning styles and academic performance in the Operational Research course of students of the IV cycle of FCAUNAC. In this sense, a questionnaire has been applied to 80 students to determine their learning styles; an exam to measure conceptual performance and another to measure procedural performance; to measure attitudinal performance, a checklist has been applied. Once obtained, the data were organized in a database, which allowed us to describe their behavior and infer the degree of association between the research variables, for which we used the Pearson correlation coefficient, the analysis of variance and Tukey's test. SPSS and Minitab were used for the calculations. The result of the research is that the more orientation towards a learning style the students obtain a higher academic performance and that there are no significant differences in the average performance of the students if we compare each type of performance with the different styles, but this does not occur the same if we make a comparison of academic performance with styles, in which case there is a superiority in visual style.